Dakwah Kiai Prostitusi Versus Kiai Petruk di Eks Lokalisasi Prostitusi Dolly Kota Surabaya - AS, Sunarto (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2019)
This article is the result of a study entitled Da’wa Kiai Prostitution versus Kiai Petruk in the Ex localization of Dolly in Surabaya. The research is focused on, first, how is the method of da’wa used by Kiai Khoiron Syu'aib (Kiai Prostitution) and Kiai Ngadimen Wahab (Kiai Petruk) in the Ex Localization of Dolly in Surabaya? second, what are the similarities and differences of the da’wa method used by both of them? Third, what is the role of both of them in merecavery of the ex-Dolalization community. Dolly is one of the biggest localizations in Southeast Asia, her fame succumbed to Surabaya as the icon of the City of Heroes. In the midst of the hustle and bustle of the lust business by the pimps and his cronies, there are some preachers who care about the fate of young women who sell love, namely the prostitutes who are localized with Dolly in Surabaya, they are Kiai Ngadimen Wahab (kiai petruk) and Kiai Khoiron Syu'aib (kiai of prostitution). Behind the menor's grooming and the beautiful appearance of the prostitutes, their hearts actually cry and scream, because most of them plunge as prostitutes because they are deceived and forced by pimps pimps and localization thugs and circumstances that force them to plunge into the valley of prostitution. In fact in the recesses of the hearts of CSWs there is a glimmer of hope to work as normal workers and become good women, positive empty space in the recesses of the hearts of CSWs is utilized and filled by the preachers of localization with a touch of humanist preaching with the principle of Rahmatan li al-alamin.